CHANGES IN THE FUNCTIONAL ACTIVITY OF THE BODY IN THE PROCESS OF HEALTH TRAINING - Uraimov Sanjar Ruzmatovich,; Tillaev Sharifjon Omonboyevich (Scholar Express Journal, 2022)
This article highlights the role of a healthy lifestyle in the transformation of the human body and the enhancement of functional capacity through wellness training
Keywords: Fitness; Healthy Lifestyle; Workouts; Health